The Adjuvanted Recombinant Zoster Vaccine Confers Long-Term Protection Against Herpes Zoster: Interim Results of an Extension Study of the Pivotal Phase 3 Clinical Trials ZOE-50 and ZOE-70. (20th July 2021) - Boutry, Céline; Hastie, Andrew; Diez-Domingo, Javier; Tinoco, Juan Carlos; Yu, Chong-Jen; Andrews, Charles; Beytout, Jean; Caso, Covadonga; Cheng, Huey-Shinn; Cheong, Hee Jin; Choo, Eun Ju; Curiac, Dan; et al.
Abstract: Background: This ongoing follow-up study evaluated the persistence of efficacy and immune responses for 6 additional years in adults vaccinated with the glycoprotein E (gE)-based adjuvanted recombinant zoster vaccine (RZV) at age ≥50 years in 2 pivotal efficacy trials (ZOE-50 and ZOE-70). The present interim analysis was performed after ≥2 additional years of follow-up (between 5.1 and 7.1 years [mean] post-vaccination) and includes partial data for year (Y) 8 post-vaccination. Methods: Annual assessments were performed for efficacy against herpes zoster (HZ) from Y6 post-vaccination and for anti-gE antibody concentrations and gE-specific CD4[2+] T-cell (expressing ≥2 of 4 assessed activation markers) frequencies from Y5 post-vaccination. Results: Of 7413 participants enrolled for the long-term efficacy assessment, 7277 (mean age at vaccination, 67.2 years), 813, and 108 were included in the cohorts evaluating efficacy, humoral immune responses, and cell-mediated immune responses, respectively. Efficacy of RZV against HZ through this interim analysis was 84.0% (95% confidence interval [CI], 75.9–89.8) from the start of this follow-up study and 90.9% (95% CI, 88.2–93.2) from vaccination in ZOE-50/70. Annual vaccine efficacy estimates were >84% for each year since vaccination and remained stable through this interim analysis. Anti-gE antibody geometric mean concentrations and median frequencies of gE-specific CD4[2+] T cells reached a plateau at approximately 6-fold above pre-vaccination levels. Conclusions: Efficacy against HZ and immune responses to RZV remained high, suggesting that the clinical benefit of RZV in older adults is sustained for at least 7 years post-vaccination. Clinical Trials Registration. NCT02723773. Abstract : Efficacy against herpes zoster and immune responses to the adjuvanted recombinant zoster vaccine plateaued at high levels between 5.1 and 7.1 years (mean) post-vaccination, suggesting that its clinical benefit in older adults is sustained for at least 7 years post-vaccination.